Improved resolution and signal-to-noise ratio performance of a confocal fluorescence microscope - Kakade, Rohan (2016)
A culmination of theory, techniques and devices stemming from a wide variety of sources and disciplines, optical microscopy presents vast possibilities for visualisation of small structures. One of the most fundamental yet significant optical microscopy techniques is Confocal Fluorescence Microscopy (CFM). CFM is studied here by analysing its performance with respect to the two most important metrics - Signal-to-noise ratio and 3D optical resolution. Several authors have commented on the inherent inefficiency of imaging systems such as CFM to utilise the available light when providing resolution beyond the well-known diffraction limit, primarily due to the precise mechanisms that help realise the resolution gain in the first place. In CFM, the detection pinhole is the key mechanism that helps realise up to 1.4 times resolution improvement over conventional wide-field microscopy techniques by trading off SNR.